Exploring the 6-year Trend in Dedicated Research Years among Integrated Plastic and Reconstructive Surgery Residents - Alexis K. Gursky, BS; Justin M. Camacho, MBA; Heli S. Patel, MBA; Meera Reghunathan, MD; Amanda A. Gosman, MD; Katharine Hinchcliff, MD (Plastic and Reconstructive Surgery, Global Open)
Background:. The plastic and reconstructive surgery (PRS) match has become more competitive with an emphasis on research productivity. With the transition of the US Medical Licensing Examination step 1 examination to pass-fail grading, alternative evaluation metrics for residency applications are needed. Our study provides a landscape of the incidence of research years amongst integrated PRS residents and the potential impacts of gender and race. Methods:. A retrospective study was conducted for all integrated PRS residents who matched between 2017 and 2022, using publicly available sources including residency websites, PubMed, Doximity, and social media. Demographics, educational background, and participation in a dedicated PRS research year were recorded. Results:. Among 993 residents across 85 accredited integrated PRS programs, 15.7% (156 of 993) took a research year, with a significant increase over 6 years (R2 = 0.73, P = 0.019). The majority were men at 51.9%, and White at 53.5%, with underrepresented in medicine residents comprising 13.5%. A total of 73.1% came from a medical school with a home program, and 52.6% matched into a top 20 residency program. No significant difference was seen in the racial/ethnic or gender representation of residents who took a research year compared with all PRS applicants and active PRS residents. Conclusions:. Research years before applying to residency are becoming more common among integrated PRS residents. Research years are especially common with students who do not have a home program and may help them gain skills and access to mentorship that improves the likelihood of matching.